Pengembangan Aplikasi E-Commerce Berbasis Mobile dengan Metode SDLC untuk PT Jagonya Ayam Merah - Haeruddin; Gautama; Gunawan (IAI Nasional Laa Roiba Bogor, 2024)
The increased use of mobile e-commerce applications prompted PT. Jagonya Ayam Merah to adopt this technology. This research develops a mobile-based e-commerce application using the SDLC method. Results indicate the application meets customer needs and provides a strong foundation for system development. SDLC is key to a structured and effective development process, expected to contribute positively to the growth of PT. Jagonya Ayam Merah's business.